Rancang Bangun Aplikasi Analisis Kepuasan Pelanggan pada Speedrocky gym Surabaya - Rafsanjani, M. Ghozali; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Speedrocky Gym Surabaya is a company which engaged in fitness services. Based on survey, there still a problem that they still don’t have questionnaire which able to measure customer satisfaction against service that Speedyrocky Gym Surabaya gives. This problem create discrepancy between member’s expectation and member’s satisfaction. The problem also affects the decreasing number of total members every month and even each year Based on the existing problems, Speedrocky Gym Surabaya requires customer satisfaction analysis application that helps in measuring the level of customer satisfaction. Applications created using gap analysis method to measure the degree to the gap between the expectations with the level of customer satisfaction, so that helps to measure the level of service of Speedrocky Gym Surabaya. Test result shows system which created can help administrators in making questionnaire also processing questionnaire answer data from the members, so that owner can find out what his members desire. Further, this application can help owner in making decision for the next period in appropriate with members desire so that it can increase service quality. All these things can be shown by analysis result that it needs improvement from parking sector and employee quality.